ANALISIS PENGARUH INFORMASI KEUANGAN, NON KEUANGAN SERTA EKONOMI MAKRO TERHADAP UNDERPRICING PADA PERUSAHAAN KETIKA IPO - Ratnasari, Anggita; Hudiwinarsih, Gunasti (Buletin Studi Ekonomi; VOL.18.NO.2.AGUSTUS 2013. (PP 85-190), 2014)
Abstract : Analisysis of the effect of financial information, non - financial and macroeconomics to company underpricing when IPO. Initial public offering (IPO) is activity of company in order to public offer of primary share sale. A company who want to go public will be doing an IPO process. Phenomenon that happened commonly is underpricing. Underpricing is conditions which show that share’s price at primary market was to low than first day of secondary market.This study aimed to analyse influence variabels which have an impact to underpricing at company when IPO in Indonesian Stock Exchange During 2007-2011. The factors studied were Return on Equity, Debt to Equity Ratio, Inflation Rate, Reputation’s Of KAP And Reputation Of Underwriter. The result of multiple regression model for this study indicates that Return on Equity, KAP Reputation and Reputation of Underwriter has a significant effect on underpricing at 5% significantly level, while financial leverage and inflation rate has no effect on underpricing.
Keywords: initial public offering (IPO), underpricing, return on equity, financial leverage, inflation rate, reputation of KAP, underwriter’s reputation.